9n-3=(n=3)+2n

Simple and best practice solution for 9n-3=(n=3)+2n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9n-3=(n=3)+2n equation:



9n-3=(n=3)+2n
We move all terms to the left:
9n-3-((n)=0

See similar equations:

| (7/x-1)=(2x-1/36) | | 18=5t+3 | | 1,000x+600=4,000 | | –2u=4u−6 | | (3j-5)=(3j+5) | | c-6=8-c | | 19s-30=s | | -3n-4=29 | | 5(c-1)+2=3(c+1)-2 | | –9+8v=9v | | 2(2x+1)=6x-20 | | 8a=123 | | -2(x-10)=30 | | 1-q=-3-2q | | 6m+5=5 | | 2z+4/3=4 | | 77=11g | | 3/4x-7+2=(x-2) | | 2x1/4x=9 | | 3(x+4)=5(x-6)+36 | | 5(k-4)+k=-8 | | x+39=90+147=360 | | 120+22x+4=15+5 | | -10-1-9w=7-6w | | r/14=3 | | 532=4z | | 4x+25=39 | | 5y/100=y-11970 | | 5(c-1)+2=3(c=+1)-2 | | 4x+10=39 | | (1/3^x)=81^-1 | | 10y–2y=64* |

Equations solver categories